EFEKTIVITAS EDUKASI GIZI MENGGUNAKAN MEDIA FLASHCARD DAN POWERPOINT TERHADAP PENGETAHUAN, SIKAP DAN PERILAKU GIZI SEIMBANG PADA SISWA SEKOLAH DASAR - Tsania, Nanda; Rahmat, Mamat; Priawantiputri, Witri; Fauziyah, Roro Nur (Jurusan Gizi Poltekkes Kemenkes Bandung, 2023)
Background: Balanced nutrition is a daily food composition that contains nutrients both types and amounts according to body needs. Balanced nutrition is needed to student for their growth period. Most of elementary school student do not know about balanced nutrition because they are still focused on the concept of “4 sehat 5 sempurna” where they think that eating rice should be more than side dishes and vegetables, even some said that drinking milk alone is enough and does not need other food. Purpose: This research aims to determine the effectiveness of providing nutrition education using flashcard and powerpoint media on increasing knowledge, attitudes and behavior of balanced nutrition in students of SDN Pasirkaliki Mandiri 2 Cimahi. Method: The research design used was a quasi-experimental with pre-test and post-test control group. The sample using purposive sampling with 62 samples. Statistical analysis using Paired T-Test, Wilcoxon and T-Independent. Results: The results shows that there is an increase in knowledge about balanced nutrition in the intervention group (p=0.000) and the control group (p=0.000), attitudes in the intervention group (p=0.014) and the control group (p=0.004), behavior in the intervention group (p=0.004) and there was no increase in behavior regarding balanced nutrition in the control group (p=0.398). Conclusion: There is no difference in the average increase in knowledge, attitudes and behavior of balanced nutrition between flashcard educational media and powerpoint media. Recommendation: Flashcard educational media needs to be redeveloped both from the appearance and from the choice of language used to attract students so as to get better results. Key words: Nutrition Education, Flashcard, Powerpoint, Balanced Nutrition